Growth of micropropagated banana plants in function of substrate and controlled release fertilizer - Rodrigues, Filipe Almendagna; Costa, Frederico Henrique da Silva; Pasqual, Moacir (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to evaluate the growth of micropropagated banana trees cv. BRS FHIA-18 in conditions of greenhouse with use of Basacote® and substrates. For the installation of the experiment, we used banana micropropagated plants cv. BRS FHIA-18. The treatments consisted of Basacote® concentrations (0, 3, 6 and 9 kgm-3 of substrate) and substrates: Plantmax® HT, Plantmax® HT + carbonized rice chaffe (CAC) and subsoil land + CAC. After 90 days of transplanting, we evaluated plant height (cm), root system length (cm), number of roots, and relationship between the dry weight (g) of shoot and roots. Plantmax® HT substrate plus 3 kg m-3 Basacote® is the most suitable for the best growth of banana trees cv. BRS FHIA-18 in the acclimatization phase.